Does The Peroneus Longus Tendon Autograft Affect The Ankle Function? A Case Series - Muhammad Hilman Bimadi; Krisna Yuarno Phatama; Edi Mustamsir (The Hip and Knee Journal, 2020)
Introduction: The peroneus longus (PL) tendon is one of the autograft choices for knee ligament injury because of its safety, length, and strength. However, studies that evaluated donor site morbidity after PL tendon graft are still limited. This case series aims to evaluate the functional outcomes of donor site morbidity after full-thickness PL tendon harvesting for knee ligament reconstruction.Presentation of Case:This study evaluated four patients who had a revision of knee ligament reconstruction surgery using PL tendon autograft from August until September 2018. The functional outcome of the donor site was evaluated before surgery, two weeks, and three months after surgery by using functional scores assessment of foot and ankle.Discussion:There are some donor sites of autograft, but several studies show that the PL tendon autograft has proven to be more favorable methods for knee ligament reconstruction based on the accessibility, safety, and strength of the harvested tendon. The studies also found that using PL tendon as an autograft, has a good result in donor site morbidity evaluation compared to others. This study provides a satisfying result on the functional outcome of the donor site morbidity evaluation.Conclusion:This study showed satisfactory functional outcomes of the foot and ankle after harvesting full-thickness PL tendon. All functional score assessment provides an excellent result in three months after surgery, although lateral ankle bulging has occurred in all patients. However, gait analysis and isokinetic test with a more significant number of patients and longer follow up periods are necessary for further study.